(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
This study investigates the application of Maslaha Mursala (public interest) within Islamic jurisprudence, specifically focusing on the Maliki school of thought. It explores how this principle, which allows for the use of public interest in legal decisions when textual evidence is lacking, has influenced various legal judgments. The research examines the traditional requirement of justice for admissibility of evidence in Islamic law, the permissibility of certain medical practices and surgical operations, and the flexibility in applying punishments and legal rules under extreme circumstances. It highlights the role of Maslaha in maintaining societal harmony and addressing contemporary issues while adhering to Islamic legal principles. The study also provides examples from Nigerian courts where Maslaha Mursala has been applied to adapt legal practices to modern needs. Overall, it underscores the adaptability of Islamic jurisprudence in addressing evolving societal challenges.